The positioning of China’s anti-corruption agencies: law enforcement or political? - Xu, Haoran (Crime, law and social change, 2025)
The positioning of China’s anti-corruption agency, the National Supervision Commission (NSC), has been widely debated due to its dual responsibilities of anticorruption enforcement and political tasks. This study aims to explore the NSC’s positioning from the perspective of law enforcement officials and examine its impact on anti-corruption enforcement and supervision powers. The findings indicate that while most officials believe that the NSC have improved the status of corruption crimes, county-level NSCs face limitations in their enforcement capacity, particularly in terms of technical investigative resources and approval authority. Additionally, some officials perceive the NSC as having higher political attributes than judicial attributes, and local party committees and party secretaries are seen as decisive factors influencing NSC enforcement. In summary, this study assesses the current status of the NSC’s positioning and enforcement as the sole anti-corruption agency in China and provides experience for further exploration of the national anti-corruption model.